Ibsen Plays : 1. - Meyer, Michael (Methuen world classics., 1994)
""Meyer's translations of Ibsen are a major fact in one's general sense of post-war drama. Their vital pace, their unforced insistence on the poetic centre of Ibsen's genius, have beaten academic versions from the field"" (George Steiner).